Body-attached sensors for automatic detection of skating stroke events in speed skating - Krumm, D.; Buder, J.; Odenwald, S. (ISEA Engineering of Sport 14 Conference, 2022)
The skating motion in speed skating consists of a skating stroke divided into the glide phase, the push-off phase and the recovery/repositioning phase [1]. Since speed skating performance depends on total power generation, which in turn is composed of work per stroke time [2], the optimization of these factors leads to an improvement of athletes' speed skating velocity. The goal of this work was to provide an algorithm that detects the skating stroke events required to evaluate key performance parameters, such as skating stroke time and cadence